Oil Price Shocks and Economic Growth in Oil-Exporting Countries : Does the Size of Government Matter? - Sadeghi, Amir (IMF Working Papers; Working Paper ;, 2017)
This paper examines the impact of government size on how output and government expenditure respond to oil price shocks in 28 oil-exporting countries between 1990 and 2016. Results suggest that if the size of government (measured by government expenditure-to-(non-oil) GDP ratio) is larger, non-oil output growth, in response to a positive oil price shock, tends to be greater and output volatility higher. Furthermore, I find that an unexpected increase in oil price leads to expansion in government expenditure and the expansion is larger, the larger is the government. This paper provides empirical evidence for direct correlation between government size and macroecnomic stability in oil-exporting countries. The findings imply that fiscal consolidation and economic diversification help to narrow down economic exposure to exogenous oil price shocks and reduce volatility in non-oil output.